Plant Conservation vs. Folk Traditions: The Case of Ophrys scolopax Cav. (Orchidaceae) in Central Western Spain - José A. González; Sonia Bernardos; Francisco Amich (Biology, 2022)
In central western Spain, the bee orchid Ophrys scolopax Cav. is limited to a few localities of the Arribes del Duero Natural Park, reaching the municipality of Villarino de los Aires (Salamanca) to the north. Due to its restricted distribution, this plant is hardly known in this territory, with the exception of this village, where it is very popular. Although most of its inhabitants are unaware of various aspects of the biology of this orchid, for example its pollination strategy, the place where the only local population grows is well-known: the Teso de San Cristóbal (“St. Christopher’s Hill”), a place of ancient pagan rituals Christianised through the construction of a hermitage. The villagers also know that its flowering period coincides with the Easter celebration, and they have traditionally looked for and collected it there during Easter Monday. This ritual has evolved over time based on the needs and interests of the community. From a religious celebration aimed at blessing the fields, it became a game among young men to obtain prestige within the community, and from the end of the 20th century to the present, it has become a festival to revitalise cultural identity. In this article, we analyse how the aforementioned traditional practices affected this orchid species in the recent past, and we describe the educational actions (conferences, workshops, courses, etc.) carried out during the last ten years so that, while maintaining the cultural practices of the village, its population should be respected and conserved at the same time.